Role Modeling and Regional Health Care Intensity: U.S. Medical Student Attitudes Toward and Experiences With Cost-Conscious Care. (May 2017) - Leep Hunderfund, Andrea N.; Dyrbye, Liselotte N.; Starr, Stephanie R.; Mandrekar, Jay; Naessens, James M.; Tilburt, Jon C.; George, Paul; Baxley, Elizabeth G.; Gonzalo, Jed D.; Moriates, Christopher; Goold, Susan D.; Carney, Patricia A.; et al.
Abstract : Purpose: To examine medical student attitudes toward cost-conscious care and whether regional health care intensity is associated with reported exposure to physician role-modeling behaviors related to cost-conscious care. Method: Students at 10 U.S. medical schools were surveyed in 2015. Thirty-five items assessed attitudes toward, perceived barriers to and consequences of, and observed physician role-modeling behaviors related to cost-conscious care (using scales for cost-conscious and potentially wasteful behaviors; Cronbach alphas of 0.82 and 0.81, respectively). Regional health care intensity was measured using Dartmouth Atlas End-of-Life Chronic Illness Care data: ratio of physician visits per decedent compared with the U.S. average, ratio of specialty to primary care physician visits per decedent, and hospital care intensity index. Results: Of 5, 992 students invited, 3, 395 (57%) responded. Ninety percent (2, 640/2, 932) agreed physicians have a responsibility to contain costs. However, 48% (1, 1416/2, 960) thought ordering a test is easier than explaining why it is unnecessary, and 58% (1, 685/2, 928) agreed ordering fewer tests will increase the risk of malpractice litigation. In adjusted linear regression analyses, students in higher-health-care-intensity regions reported observing significantly fewer cost-conscious role-modeling behaviors: For each one-unit increase in the three health care intensity measures, scores on the 21-point cost-conscious role-modeling scale decreased by 4.4 (SE 0.7), 3.2 (0.6), and 3.9 (0.6) points, respectively (all P < .001). Conclusions: Medical students endorse barriers to cost-conscious care and encounter conflicting role-modeling behaviors, which are related to regional health care intensity. Enhancing role modeling in the learning environment may help prepare future physicians to address health care costs. Abstract : Supplemental Digital Content is available in the text.